Search for a heavy vector resonance decaying to a Z boson and a Higgs boson in proton-proton collisions at √s = 13 TeV - Sirunyan, A. M. (2021)
A search is presented for a heavy vector resonance decaying into a Z boson and the standard model Higgs boson, where the Z boson is identified through its leptonic decays to electrons, muons, or neutrinos, and the Higgs boson is identified through its hadronic decays. The search is performed in a Lorentz-boosted regime and is based on data collected from 2016 to 2018 at the CERN LHC, corresponding to an integrated luminosity of 137fb−1. Upper limits are derived on the production of a narrow heavy resonance Z′, and a mass below 3.5 and 3.7TeV is excluded at 95% confidence level in models where the heavy vector boson couples predominantly to fermions and to bosons, respectively. These are the most stringent limits placed on the Heavy Vector Triplet Z′ model to date. If the heavy vector boson couples exclusively to standard model bosons, upper limits on the product of the cross section and branching fraction are set between 23 and 0.3fb for a Z′ mass between 0.8 and 4.6TeV, respectively. This is the first limit set on a heavy vector boson coupling exclusively to standard model bosons in its production and decay.